Alternative Generation of CNS Neural Stem Cells and PNS Derivatives from Neural Crest‐Derived Peripheral Stem Cells. (February 2015) - Weber, Marlen; Apostolova, Galina; Widera, Darius; Mittelbronn, Michel; Dechant, Georg; Kaltschmidt, Barbara; Rohrer, Hermann
Abstract Neural crest‐derived stem cells (NCSCs) from the embryonic peripheral nervous system (PNS) can be reprogrammed in neurosphere (NS) culture to rNCSCs that produce central nervous system (CNS) progeny, including myelinating oligodendrocytes. Using global gene expression analysis we now demonstrate that rNCSCs completely lose their previous PNS characteristics and acquire the identity of neural stem cells derived from embryonic spinal cord. Reprogramming proceeds rapidly and results in a homogenous population of Olig2‐, Sox3‐, and Lex‐positive CNS stem cells. Low‐level expression of pluripotency inducing genes Oct4, Nanog, and Klf4 argues against a transient pluripotent state during reprogramming. The acquisition of CNS properties is prevented in the presence of BMP4 (BMP NCSCs) as shown by marker gene expression and the potential to produce PNS neurons and glia. In addition, genes characteristic for mesenchymal and perivascular progenitors are expressed, which suggests that BMP NCSCs are directed toward a pericyte progenitor/mesenchymal stem cell (MSC) fate. Adult NCSCs from mouse palate, an easily accessible source of adult NCSCs, display strikingly similar properties. They do not generate cells with CNS characteristics but lose the neural crest markers Sox10 and p75 and produce MSC‐like cells. These findings show that embryonic NCSCs acquire a full CNS identity in NS culture. In contrast, MSC‐like cells are generated from BMP NCSCs and pNCSCs, which reveals that postmigratory NCSCs are a source for MSC‐like cells up to the adult stage. Stem Cells2015;33:574–588